Analisis Preferensi Konsumen terhadap Buah Jeruk Impor dan Buah Jeruk Lokal di Kota Denpasar, Bali - KADEK YUNNI DWIASTARI; KETUT BUDI SUSRUSA; NI WAYAN PUTU ARTINI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
Analysis of Consumer Preference on Imported Citrus Fruit and Local Citrus Fruitin Denpasar, Bali. This study aims to determine consumer preferences in buying citrus fruits in DenpasarCity, and to find out the attributes of citrus fruits that are most dominantly chosen byconsumers in purchasing decisions. The location of this research was conducted in PasarBadung, Sanglah Market, Ketapian Market, and Pasar Kreneng which were determinedpurposively. Data collection method by distributing questionnaires to respondents. Thepopulation in this study are consumers of fruit buyers who have at least consumed andbought citrus fruits. The sample of this study amounted to 50 people conducted byaccidental sampling method. The results in this study indicate respondents' preference inbuying citrus fruits, as many as 35 (70%) people choose local oranges and 15 (30%)people choose imported oranges. In determining their preferences there are severalindicators that influence respondents to choose the type of citrus fruit. Of the sevenindicators namely taste, color, fruit size, price, personal taste, income level andavailability continuity that most influence the respondents to choose the type of citrusthat is preferred is the good fruit taste from respondents who choose local oranges andimported oranges. The fruit flavor indicator has the largest percentage of 71.42% forlocal oranges and 86.66% for imported oranges. The most dominant attribute chosen byconsumers in buying local citrus fruits and imported oranges is the attribute of fruitflavor. Where the attributes of taste are the main consideration of respondents in buyingcitrus fruit compared to other attributes such as color, shape, cleanliness, size, price, texture, and freshness of fruit.